(untitled) (American Journal of Life Science and Innovation, 2025)
Malaria during pregnancy is a significant public health problem in endemic countries. This study aimed to determine the prevalence of malaria and associated risk factors among pregnant women attending the Departmental Hospital of Ntoum (Northwest Gabon) for prenatal care. A cross-sectional survey was conducted for 6 months (July to December 2024), among pregnant women attending the prenatal care unit of the Ntoum departmental Hospital (NDH). Pregnant women selected for the study were asked to complete a structured questionnaire. At the end of the interview, a nurse drew a blood sample in an EDTA tube. Malaria was detected by thick blood smear using the WHO method. A P-value < 0.05 was considered statistically significant. Blood samples were collected from 202 pregnant women. Malaria was diagnosed in 23.3%. Patients aged between 20 and 30 years (53.2%), with a gestation of 4 to 6 months (46.8%) and living in the first district of Ntoum city (70.2%) were the most infected with the disease. Most of these women had completed secondary education (87.2%) and were unemployed (68.1%). Fever and headache were the most frequently reported symptoms, accounting for 51.1% and 42.5% of cases, respectively. Women who slept under an insecticide-treated net or used insecticide spray were less prone to malaria infection; but, the difference was not significant (P˃0.05) In contrast, pregnant women who reported episodes of fever were significantly less likely to test positive to malaria (OR = 0.24 [0.09 - 0.61]; P =0.002). Among the women who tested positive, 83% had a low parasitemia. Plasmodium infection in the Komo Mondah department is high. The development of a malaria vaccine would make it possible to immunize all participants and thus reduce the spread of malaria worldwide.